Establishing a Profound Educator Resource Management: Teacher’s Performance Development Standpoint - Sofyan Tsauri (The Faculty of Education and Teaching Training, 2022)
Education is one of the factors that affect the quality of a nation. Quality education is obtained from qualified educator resources. In other words, educator resources have a significant role in advancing the nation. This research focuses on how Educator Resource Planning, recruitment and selection, training and development, and performance appraisal improve teacher performance in SMP Islam An-Nur Rambipuji Jember. This study uses a descriptive qualitative approach to the type of case study research. Observation, interviews, and documentation did data collection. The Data were analyzed using an interactive model created by Miles, Huberman, and Saldana. The study produced four findings. First, the school analyzes the teaching load and the needs of teachers. Second, the school creates a recruitment and selection committee. The committee analyzes the position, the committee determines the recruitment source, job information is disseminated through several media, and the selection is carried out through administrative selection and interviews. Third, teachers participate in teacher forums, seminars and workshops, and training held by internal and external institutions. Fourth, principals and staff assess teacher attendance, teacher teaching and learning processes, quality assurance achievements, and additional work given to teachers. Pendidikan menjadi salah satu faktor yang mempengaruhi kualitas suatu bangsa. Pendidikan yang berkualitas diperoleh dari sumber daya pendidik yang berkualitas. Dengan kata lain, sumber daya pendidik memiliki peran yang signifikan dalam memajukan bangsa. Penelitian ini difokuskan untuk menemukan bagaimana perencanaan sumber daya pendidik, rekrutmen dan seleksi, pelatihan dan pengembangan, serta penilaian kinerja untuk meningkatkan kinerja guru di SMP Islam An-Nur Rambipuji Jember. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan jenis penelitian studi kasus. Pengumpulan data dilakukan dengan observasi, wawancara, dan dokumentasi. Data dianalisis dengan menggunakan model interaktif yang dibuat oleh Miles, Huberman, dan Saldana. Penelitian ini menghasilkan empat temuan. Pertama, sekolah menganalisis beban mengajar dan kebutuhan guru. Kedua, sekolah membuat panitia rekrutmen dan seleksi, panitia melakukan analisis jabatan, panitia menentukan sumber rekrutmen, informasi lowongan kerja disebarkan melalui beberapa media, dan seleksi dilakukan dengan seleksi administrasi dan wawancara. Ketiga, guru mengikuti forum guru, seminar dan lokakarya, dan pelatihan yang diadakan oleh lembaga internal dan eksternal. Keempat, kepala sekolah dan jajarannya menilai kehadiran guru, proses belajar mengajar guru, pencapaian penjaminan mutu, dan pekerjaan tambahan yang diberikan kepada guru.